El Modelo de Difusión Tecnológica y la Producción Silvícola: el Caso de Productores Forestales de Valdivia, Chile. - Amtmann, Carlos A.; Fernández, Francisco; Moraga, Jubel (Bosque (Valdivia), 1977)
The diffusion process of two types of technical innovations in a population of sixty timber producers of the Valdivia Province was analyzed. The adoption rate was 78% for the motorsaw and 26% for modern plantation tools. When the sociodemographic attributes of adopters and nonadopters were studied, the generalizations of the diffusion of innovations model were confirmed. The results were discussed ín relation to other studies of technological diffusion in systems with other functions, emphasizing the lack of empirical sociological Information about the diffusion of techniques in forestry.